Bioactive sialylated-mucin (SiaMuc) glycopeptide produced from enzymatic hydrolysis of edible swiftlet’s nest (ESN): degree of hydrolysis, nutritional bioavailability, and physicochemical characteristics - Tan, Hui Yan; Sue, Lian Mun; Jia, Lin Lee; Seng, Joe Lim; Daud, Nur Aliah; Babji, Abdul Salam; Sarbini, Shahrul Razid (Taylor and Francis, 2022)
The swiftlet’s nest is an edible bird’s nest (EBN) produced from dried gelatinized saliva secreted by swiftlets during the breeding season. It is widely used in industries for its high nutritional values and health benefits. However, the utilization of ESN is restricted due to its physicochemical properties, such as insolubility. The recently invented bioactive ESN hydrolyzate is reported to improve the ESN’s solubility, functional and nutritional properties to broaden its application. This study has produced bioactive ESN hydrolyzates with different hydrolysis periods to investigate the optimum conditions to achieve maximized degree of hydrolysis (DH) and to compare the physicochemical differences. The result revealed that optimum ESN hydrolysis was at 90 minutes, in which the DH and enhanced solubility (three folds) indicated a complete breakdown of glycoprotein into bioactive glycopeptide. This result is in line with the physicochemical analyses result. The hydrolysis has significantly decreased (p ≤ .05) the ESN protein content, while the levels for peptide, glycopeptide, polysaccharides, and sialic acid showed the opposite. Interestingly, the amino acid from raw ESN and hydrolyzates in all incubation periods showed no significant difference (p ≤ .05). This result suggests that the ESN biological properties remained unchanged with alcalase hydrolysis. Therefore, the findings in this study confirm the feasibility of bioactive ESN hydrolyzate as a versatile product suitable for various industries in utilizing ESN in whole instead of as extracts.